The road from Mont Pèlerin : the making of the neoliberal thought collective - Mirowski, Philip, 1951- 1951- (Harvard Univ. Press, 2009)
"What exactly is neoliberalism, and where did it come from? This volume attempts to answer these questions by exploring neoliberalism's origins and growth as a political and economic movement. Although modern neoliberalism was born at the "Colloque Walter Lippmann" in 1938, it only came into its own with the founding of the Mont Pèlerin Society, a partisan "thought collective," in Vevey, Switzerland, in 1947. The Road from Mont Pèlerin presents the key debates and conflicts that occurred among neoliberal scholars and their political and corporate allies regarding trade unions, development economics, antitrust policies, and the influence of philanthropy. The book captures the depth and complexity of the neoliberal "thought collective" while examining the numerous ways that neoliberal discourse has come to shape the global economy." -- Book jacket.